Sampling Unit in Phytosociological Studies - Khan, M. A. Waheed (Indian Forester, 1958)
Necessity for detailed phytosociologicai studies is stressed to build up a classification of Indian Vegetation on a more sound basis. As these studies are made only in representative areas of limited extent, selection of a suitable sampling unit is imperative. Factors influencing the shape, size and number of sampling units are discussed, and the latest methods of vegetational surveys, designed for Indian conditions, are reviewed. A typical study of this nature was made in the sal forests of Madhya Pradesh, and accordingly improvements are suggested over the existing practices.